Accumulation of follicular CD8+ T cells in pathogenic SIV infection - Ferrando-Martinez, Sara; Moysi, Eirini; Pegu, Amarendra; Andrews, Sarah; Makamdop, Krystelle Nganou; Ambrozak, David; McDermott, Adrian B.; Palesch, David; Paiardini, Mirko; Pavlakis, George N.; Brenchley, Jason M.; Douek, Daniel; et al. (Journal of Clinical Investigation, 2018)
LN follicles constitute major reservoir sites for HIV/SIV persistence. Cure strategies could benefit from the characterization of CD8+ T cells able to access and eliminate HIV-infected cells from these areas. In this study, we provide a comprehensive analysis of the phenotype, frequency, localization, and functionality of follicular CD8+ T cells (fCD8+) in SIV-infected nonhuman primates. Although disorganization of follicles was a major factor, significant accumulation of fCD8+ cells during chronic SIV infection was also observed in intact follicles, but only in pathogenic SIV infection. In line with this, tissue inflammatory mediators were strongly associated with the accumulation of fCD8+ cells, pointing to tissue inflammation as a major factor in this process. These fCD8+ cells have cytolytic potential and can be redirected to target and kill HIV-infected cells using bispecific antibodies. Altogether, our data support the use of SIV infection to better understand the dynamics of fCD8+ cells and to develop bispecific antibodies as a strategy for virus eradication.
CRIS-Team Scopus Importer:2024-09-09